Phytochemical Investigation and Antimicrobial Evaluation of Foeniculum vulgare Leaves Extract Ingredient of Ethiopian Local Liquor - Seid, Mohammed; Dekebo, Aman; Babu, Neelaiah (Journal of Pharmacy and Nutrition Sciences, 2018)
Medicinal plants are of great interest to the researcher in the field of biotechnology, as natural products, including medicinal plants, accounts 25% of prescribed drugs. Plants are sources for fragrances, drink colors and flavors in several countries including Ethiopia. All parts of Foeniculum vulgare were traditionally used as antispasmodic, aromatic, carminative, digestive, galactagogues, stomach and kidney ailment. Foeniculum vulgare leaves extract was investigated for its phytochemicals as well as antimicrobial effects. The petroleum ether, CHCl3, CHCl3/CH3OH (1:1) and CH3OH crude extract were subjected to phytochemicals screening test which revealed that it is rich in any primary and secondary metabolites such as steroids, tannins, flavonoids, cholesterol, terpenoids, saponins, phenols, cardiac glycosides, carbohydrates, and proteins. The essential oil of the plant leaves was investigated by GC?MS and was found to have (64.92%) anethole, as a major constituent followed by (30.88%) estragole and (3.21%) fenchyl acetate. The crude extracts, oil, and the isolated compound were tested against four bacterial species (Gram negative bacteria, Escherichia coli and Shigella flexneri; Gram positive bacteria: Staphylococcus aureus and Streptococcus pyrogenes) and two fungal species (Fusarium oxysporum and Aspergillus niger) using paper disc diffusion method. Tests of antimicrobial activity showed that all crude extracts and isolated pure compound were active against all the tested bacterial and fungal species. However, the hydrodistillation extract was found to have no antibacterial activity towards the tested bacterial species but active against the two fungal species and thus the present study supported the traditional claims of the plant.